Application of eHealth Self-Management (eHSM) for clients hypertension - Kusumawaty, Jajuk; Anwar, Syamsul; Herlina, Lily; Yunitri, Ninik; Supriadi, Dedi; Rosmiati, Rosmiati (Science Midwifery, 2024)
Hypertension is a cardiovascular disease and is one of the main causes of premature death throughout the world. The aim of this research is to determine the effect of eHealth Self-Management (eHSM) intervention on reducing blood pressure in adult clients with hypertension. Method on The implementation of Evidence Base Nursing (EBNP) Practice was carried out in the Linggasari sub-district, Ciamis Regency. The number of respondents was 30 people, four times a month they were given education in the Linggasari area, carried out with a pretest at the beginning and a posttest at the end of the intervention, monthly telephone counseling was carried out for 4 weeks, education took place in 4 meetings every week with a duration of approximately 60 minutes in each session. to remind you to take your medication every night. Each counseling session lasts approximately 20 minutes via telephone via WhatsApp. Based on the Wilcoxon test results in the table using spss.16, the blood pressure results before and after implementing e-health gave significant results because the p value is 0.000, which is smaller than the Alpha value (<0.05), so Ho is rejected, which means there is a difference in blood pressure. before and after implementing e-health. Conclusion There is a significant effect of the eHealth Self Management (eHSM) intervention with the What App Group application on hypertensive clients in the Linggasari sub-district of the Ciamis Health Center Work Area.